The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1104/pp.114.3.1071
|View full text |Cite
|
Sign up to set email alerts
|

A cDNA Clone Highly Expressed in Ripe Banana Fruit Shows Homology to Pectate Lyases

Abstract: A cDNA clone (Banl7), encoding a protein homologous to pectate lyase, has been isolated from a cDNA library from climacteric banana fruit by means of differential screening. Northern analysis showed that Banl7 mRNA is first detected in early climacteric fruit, reaches a steady-state maximum at the climacteric peak, and declines thereafter in overripe fruit. Accumulation of the Banl7 transcript can be induced in green banana fruit by exogenous application of ethylene. This demonstrates that expression of this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 33 publications
2
55
0
Order By: Relevance
“…This is similar to the expression of three transcripts (plA, plB, and plC) encoding PLs in strawberry fruit 25 and two genes encoding PLs in the pulp of ripe banana fruit 26,27 . Exogenous ethylene induced accumulation of Banl7 transcript encoding a PL in green banana fruit 26 is similar to the hastening of MzPL expression now found in ethylene-treated sapodilla fruit. In strawberry, the expression of a gene encoding a PL was reduced by antisense expression.…”
Section: Discussionsupporting
confidence: 70%
“…This is similar to the expression of three transcripts (plA, plB, and plC) encoding PLs in strawberry fruit 25 and two genes encoding PLs in the pulp of ripe banana fruit 26,27 . Exogenous ethylene induced accumulation of Banl7 transcript encoding a PL in green banana fruit 26 is similar to the hastening of MzPL expression now found in ethylene-treated sapodilla fruit. In strawberry, the expression of a gene encoding a PL was reduced by antisense expression.…”
Section: Discussionsupporting
confidence: 70%
“…PL makes a contribution to the degradation of pectin and fruit ripening and softening (Dominguez-Puigjaner et al 1997;Marin-Rodriguez et al 2002). It was of significance to carry out comparative analysis of PL activity and PL gene expression during strawberry fruit ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Pectate lyase (PL, EC 4.2.2.2), is an enzyme that catalyzes the eliminative cleavage of (1→4)-alpha-D-galacturonan methyl ester to give oligosaccharides with 4-deoxy-6-Omethyl-alpha-D-galact-4-enuronosyl groups at their nonreducing ends (Marin-Rodriguez et al 2002). In plants, it that has been confirmed that PL participates in the degradation of the backbone of pectic polysaccharides during ripening and softening of climacteric fruits such as bananas (Dominguez-Puigjaner et al 1997;MarinRodriguez et al 2002MarinRodriguez et al , 2003Payasi and Sanwal 2003;Payasi et al 2004). However, little information is available concerning the role and activity of PL in strawberries during ripening and softening.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes catalyze the cleavage of unesterified galacturonosyl linkages by a b-elimination reaction. Ripening-related PL genes have been identified in banana (Domínguez-Puigjaner, Llop, Vendrell, & Prat, 1997), grape (Nunan, Davies, Robinson, & Fincher, 2001) and strawberry (Benítez-Burraco et al, 2003;Medina-Escobar, Cárdenas, Moyano, Caballero, & Muñoz-Blanco, 1997). More interestingly, suppression of the mRNA of this gene in strawberry by an antisense transformation increased significantly the firmness of ripe fruits and extended the postharvest shelf life (Jiménez-Bermú dez et al, 2002).…”
Section: Introductionmentioning
confidence: 96%